2010
DOI: 10.2527/jas.2009-2544
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of genetic influences to animal-to-animal variation in myoglobin content and beef lean color stability1

Abstract: Longissimus thoracis steaks from steers (n = 464) with 0 to 50% inheritance of Angus, Charolais, Gelbvieh, Hereford, Limousin, Red Angus, and Simmental were evaluated during 6 d of display to assess genetic contributions to color stability. Color space values [CIE L* (lightness), a* (redness), b* (yellowness)], chroma, color change (DeltaE), and surface metmyoglobin (K/S 572/525) were determined on d 0 and 6 of display. Myoglobin concentration was highly heritable (0.85), but ultimate pH was weakly heritable (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 36 publications
4
28
0
3
Order By: Relevance
“…While this study does not identify a breed effect in regard to total muscle iron, non-heme iron, nor heme iron, King et al (2010) found that myoglobin concentration in LT steak was highly heritable (h 2 = 0.85) and myoglobin did vary among breeds with myoglobin concentration higher in Gelbvieh, Red Angus, and Simmental than in Charolais and Limousin cattle.…”
Section: Breed Effect On Mineral Concentrationmentioning
confidence: 86%
“…While this study does not identify a breed effect in regard to total muscle iron, non-heme iron, nor heme iron, King et al (2010) found that myoglobin concentration in LT steak was highly heritable (h 2 = 0.85) and myoglobin did vary among breeds with myoglobin concentration higher in Gelbvieh, Red Angus, and Simmental than in Charolais and Limousin cattle.…”
Section: Breed Effect On Mineral Concentrationmentioning
confidence: 86%
“…King et al (2010) reported that there was substantial animal-to-animal variation (within a species and breed) in beef color and that animal-to-animal differences played a larger role in the capacity of the muscle to maintain its color, rather than in its initial color. Furthermore, these authors highlighted the existence of opportunities to improve color stability through genetic selection.…”
Section: Animal-to-animal Variationmentioning
confidence: 99%
“…Thus, color stability research has focused on differences due to ante-or postmortem management (Ledward, 1985;Lawrence et al, 2004;Mancini et al, 2008) and across muscles (Talmant and Monin, 1986;McKenna et al, 2005). However, previous work from our laboratory has substantiated the importance of animal variation and indicated that genetic influences contribute to animal variation in lean color stability (King et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, given the evidence that these factors also vary substantially within the LM and contribute to variation in color stability in the LM (King et al, 2010(King et al, , 2011, it appears that significant opportunity exists to use genetic selection and management to reduce animal variation in color stability. The present experiment was conducted to characterize the relative contribution of animal and muscle effects to beef lean color stability.…”
Section: Introductionmentioning
confidence: 99%